If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(-2x + -4) = 97 + 3(4x + 5) Reorder the terms: 5(-4 + -2x) = 97 + 3(4x + 5) (-4 * 5 + -2x * 5) = 97 + 3(4x + 5) (-20 + -10x) = 97 + 3(4x + 5) Reorder the terms: -20 + -10x = 97 + 3(5 + 4x) -20 + -10x = 97 + (5 * 3 + 4x * 3) -20 + -10x = 97 + (15 + 12x) Combine like terms: 97 + 15 = 112 -20 + -10x = 112 + 12x Solving -20 + -10x = 112 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -20 + -10x + -12x = 112 + 12x + -12x Combine like terms: -10x + -12x = -22x -20 + -22x = 112 + 12x + -12x Combine like terms: 12x + -12x = 0 -20 + -22x = 112 + 0 -20 + -22x = 112 Add '20' to each side of the equation. -20 + 20 + -22x = 112 + 20 Combine like terms: -20 + 20 = 0 0 + -22x = 112 + 20 -22x = 112 + 20 Combine like terms: 112 + 20 = 132 -22x = 132 Divide each side by '-22'. x = -6 Simplifying x = -6
| logx+log(4x-3)=1 | | 13=x^2-14x | | 32w-8w+21=69 | | 9y-15=-3(y+7) | | 22590-x=17500 | | 46t-9t+7t-40t+12=96 | | T(x)=2x^2+8x+6 | | 7x+12y=1 | | 62=5x | | 6p+14q= | | 4k+k-2k+8=86 | | 25-8x=1 | | -2p+24=13 | | 5x+8=6x-21 | | 92m-62m-23m-4m-m+7=95 | | 45-14y=5+6y | | 15=-4d+3 | | 39k-21k-6k-4k-7k=42 | | 14-4y=10 | | (2+y)(5y-4)=0 | | 5a+2=-18 | | 1.25x+12y=60 | | 3=-7k+3 | | -6f+8=2 | | 21=4b-7 | | 5(2x-3)=11 | | 8k-4=4 | | 3x-10=10-x | | 7n+9=2 | | 2g-g=97 | | 5p^2+7p-4-3p-2p^2+6= | | 78=9u-3 |